2012
DOI: 10.1371/journal.pone.0037935
|View full text |Cite
|
Sign up to set email alerts
|

Combination of RGD Compound and Low-Dose Paclitaxel Induces Apoptosis in Human Glioblastoma Cells

Abstract: BackgroundIntegrins are a family of transmembrane adhesion proteins that mediate cell adhesion and intracellular signaling. Integrin-αvβ3 is expressed on the surface of human glioblastoma cells, and can be further induced by chemical stress. The Arg-Gly-Asp (RGD) motif-containing peptides are specifically bound to integrin-αvβ3, and to inhibit neovasculature underlying competition to normal extracellular matrix proteins. This study employed two types of RGD peptides, cyclic RGD (c(RGDyK)) and bi-cyclic RGD (E[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Similarly to our data, several studies have revealed that RGD-conjugated drugs have more significant curative effects on GBM cells when compared to unmodified compounds [ 44 , 45 , 46 ]. Furthermore, Xin and co-authors demonstrated that exosomes functionalised with RGD had favourable gastric-tumour-targeting properties [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly to our data, several studies have revealed that RGD-conjugated drugs have more significant curative effects on GBM cells when compared to unmodified compounds [ 44 , 45 , 46 ]. Furthermore, Xin and co-authors demonstrated that exosomes functionalised with RGD had favourable gastric-tumour-targeting properties [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…As ␣v␤3 integrin is thought to be important for GBM progression, invasion, and survival, inactivation or suppression of this integrin may be sufficient to induce cell death (45). Consistent with the observed cytotoxicity of anti-EMP2 antibodies, downregulation of ␣v␤3 integrin by tumistatin or RGD peptides has been shown to induce apoptosis (46,47). In the case of tumistatin, apoptosis is induced via dampening of AKT signaling, and whether anti-EMP2 therapy has a similar effect on AKT signaling is currently being studied by our group.…”
Section: Discussionmentioning
confidence: 77%
“…Changes in integrin expression in response to chemotherapy can be exploited to increase response to anti-integrin therapeutics [175]. However, changes in expression could also render a targeted therapeutic ineffective therefore incorporation of an integrin antagonist into existing or novel drug combinations will require prior assessment of their effects on integrin expression at the preclinical stage.…”
Section: Changes In Integrin Expression In Response To Therapymentioning
confidence: 99%